Stock Price as an Intervening Variable That Influencing Solvency, Inflation, and Financial Distress on Firm Value - SUTISMAN, Entar; PRASETIANINGRUM, Septyana; LANDE, Adriani; SUTISNA , Entis; B, St. Mariani (Journal of Governance, Taxation and Auditing, 2024)
This study aims to analyze the effect of solvency, inflation, and financial distress on firm value with stock price as an intervening variable in manufacturing companies in the consumer goods sector during the 2020-2023 period. The data used in this study comes from the financial statements of companies listed on the Indonesian Stock Exchange. The analysis method used is path analysis with a quantitative approach. The population in this study is manufacturing industry companies in the consumer goods sector listed on the Indonesia Stock Exchange that have experienced a decline in profits during the years 2020-2023. The sampling technique used was purposive sampling and resulted in 30 out of a total of 91 companies in the consumer goods sector. Data analysis was carried out through descriptive analysis, outer model analysis, inner model analysis and hypothesis testing using SmartPLS v.3.2.9 software assistance. The results showed that solvency and financial distress had a significant effect on stock prices. Solvency, financial distress and stock prices have a significant effect on firm value; inflation has no significant effect on stock prices and firm value. Stock prices are unable to mediate the effect of solvency, inflation, and financial distress on firm value. This shows that these factors can affect firm value directly without having to go through stock prices.